4-4x=-3x

Simple and best practice solution for 4-4x=-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-4x=-3x equation:


Simplifying
4 + -4x = -3x

Solving
4 + -4x = -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
4 + -4x + 3x = -3x + 3x

Combine like terms: -4x + 3x = -1x
4 + -1x = -3x + 3x

Combine like terms: -3x + 3x = 0
4 + -1x = 0

Add '-4' to each side of the equation.
4 + -4 + -1x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -1x = 0 + -4
-1x = 0 + -4

Combine like terms: 0 + -4 = -4
-1x = -4

Divide each side by '-1'.
x = 4

Simplifying
x = 4

See similar equations:

| 18(k+12)=936 | | 2x+3x+3x+32=360 | | 14(x+30)=-196 | | v/9-5=(-6) | | z2=9/16 | | 19=-9(8c-3) | | 7v+1+6v= | | 2g+2g-4=43 | | 3-3(x-4)=-3-2 | | b/9=3 | | -3(x+7)=6x-39 | | -10+9k=62 | | 5x^2-14x-76=0 | | x-.10x=150 | | 7(8x+8)=56x-1 | | 13-50=20(5x-9x)+6x | | -1-(-12)= | | 8t/6 | | 2*15/7 | | cbrt(2x-3)=3 | | 11-12x=-11s | | 4(-3x)+y=2 | | 0.166666667x=4 | | 15y+9x=30 | | 8y+7=9y-1 | | 52=4(s-67) | | 5-5cosx=0 | | 9*b+4=7 | | -26-49= | | -8(-3-2n)=104 | | -7+2(1-5s)=35 | | 9*-b+4=7 |

Equations solver categories